2011
DOI: 10.1254/jphs.10173fp
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin and Pregabalin Inhibit the Itch-Associated Response Induced by the Repeated Application of Oxazolone in Mice

Abstract: Abstract. We investigated the effects of gabapentin and pregabalin on the itch-associated response in a mouse model of chronic dermatitis induced by the repeated application of 4-ethoxymethylene-2-phenyl-2-oxazolin-5-one (oxazolone). Challenging the mice with oxazolone-induced chronic dermatitis with the oxazolone evoked severe and transient scratching behavior until 1 h after the application of oxazolone. Thereafter, a more mild and continuous scratching behavior was also observed for at least 8 h. Both sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
0
8
0
2
Order By: Relevance
“…In a mouse model of oxazolone induced chronic atopic dermatitis, treatment with pregabalin and gabapentin decreased scratching behaviors, and authors of this study suggested that the antipruritic effects of these drugs may be because of the binding to the α2δ subunit of the voltage-gated calcium channels in the dorsal root ganglion of the spinal cord (13).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…In a mouse model of oxazolone induced chronic atopic dermatitis, treatment with pregabalin and gabapentin decreased scratching behaviors, and authors of this study suggested that the antipruritic effects of these drugs may be because of the binding to the α2δ subunit of the voltage-gated calcium channels in the dorsal root ganglion of the spinal cord (13).…”
Section: Introductionmentioning
confidence: 74%
“…Although different sensory neurons and pathways mediate the sensation of pain and itch, there are some common mediators and receptors in the both systems (13)(14)(15). Because of these similarities it has been suggested that drugs such as pregabalin which is an effective medication in the reduction of the neuropathic pains (2,(16)(17)(18)(19)(20) may have potential benefits in decreasing the itch severity, especially the neuropathic one.…”
Section: Introductionmentioning
confidence: 99%
“…The close relationship between these pathways suggests that pregabalin may inhibit the sensation of itching. In particular, the results of experiments on mice suggest that pregabalin may exert an antipruritic effect through α 2 δ‐1 subunit binding of voltage‐gated Ca 2 (+) channels and the up‐regulation of the α 2 δ‐1 subunit in dorsal root ganglion 19 . There is evidence of successful use of pregabalin in neuropathic itch 20 and in uraemic pruritus in haemodialysis patients 17 …”
Section: Resultsmentioning
confidence: 99%
“… identified that vagus nerve stimulation reduces pruritus in humans. Last but not least, gabapentin and pregabalin which alleviate symptoms of pain and itch have also been reported to improve cardiac autonomic function by augmenting the parasympathetic tone .…”
Section: Our Hypothesis – ‘An Aberrant Parasympathetic Nervous Systemmentioning
confidence: 99%